Green Extraction of Polyphenols from Waste Bentonite to Produce Functional Antioxidant Excipients for Cosmetic and Pharmaceutical Purposes: A Waste-to-Market Approach - Giulia Di Prima; Elena Belfiore; Martina Migliore; Amalia Giulia Scarpaci; Giuseppe Angellotti; Ignazio Restivo; Mario Allegra; Vincenzo Arizza; Viviana De Caro (MDPI AG, 2022)
In an ever-growing perspective of circular economy, the development of conscious, sustainable and environmental-friendly strategies to recycle the waste products is the key point. The scope of this work was to validate the waste bentonite from the grape processing industries as a precious matrix to extract polyphenols by applying a waste-to-market approach aimed at producing novel functional excipients. The waste bentonite was recovered after the fining process and opportunely pre-treated. Subsequently, both the freeze dried and the so-called "wet" bentonites were subjected to maceration. PEG200 and Propylene Glycol were selected as solvents due to their ability to dissolve polyphenols and their wide use in the cosmetic/pharmaceutical field. The extracts were evaluated in terms of yield, density, pH after water-dilution, total phenolic (Folin-Ciocalteu) and protein (Bradford) contents, antioxidant power (DPPH), amount of some representative polyphenols (HPLC-DAD), cytocompatibility and stability. Both solvents validated the bentonite as a valuable source of polyphenols and led to colored fluids characterized by an acidic pH after water-dilution. The best extract was obtained from the wet bentonite with PEG200 and highlighted the highest phenolic content and consequently the strongest antioxidant activity. Additionally, it displayed proliferative properties and resulted almost stable over time. Hence, it might be directly used as polyphenols-enriched functional novel raw material for cosmetic and pharmaceutics purposes.